SIKAP MASYARAKAT TERHADAP PRODUK DETERJEN DI KOTA YOGYAKARTA - Wendri Rusli (Fakultas Bisnis Universitas Kristen Duta Wacana, 2011)
ABSTRACT This study examines the effect of advertisement, brand, dan product quality on society attitude in Yogyakarta. The sample is drawn with a stratified random precedure, resulted on the respondents 100 from yogyakarta society. Using Ajzen and Fishbein analysis, the results show that advertisement, brand, and product quality influence on society’s attitude in Yogyakarta. Keywords: Advertisement, Brand, Product Quality, Attitude